The Effectiveness of a Local Wisdom-Based Children’s Literature Module to Enhance Short Story Writing Skills in Grade IV Elementary Students - Lintang Kironoratri; Much Arsyad Fardani; Rani Setiawaty; Imaniar Purbasari; Isnaini Khalimatus Sa’diyah; Kurnia Wulandari (AL-ISHLAH: Jurnal Pendidikan, 2025)
Writing instruction in Indonesian elementary schools often relies on traditional methods such as lectures and rote exercises, resulting in low student engagement and underdeveloped writing skills. This study aimed to evaluate the effectiveness of a children’s literature module incorporating Grobogan local wisdom in enhancing short story writing skills among Grade IV students at SDN 1 Penganten. A quantitative pre-experimental approach was employed using a one-group pretest-posttest design. A total of 27 students participated in the intervention. Writing skills were assessed before and after the use of the module. Data were analyzed using the Shapiro-Wilk test for normality, paired sample t-test to assess significance, and N-Gain to measure learning improvement. Results indicated that both pretest and posttest data were normally distributed (p 0.05), validating the use of parametric testing. The paired t-test showed a statistically significant improvement in writing performance (p = 0.000). The average N-Gain score of 0.47 falls within the moderate improvement category, suggesting that the module was effective in enhancing students’ writing skills. The integration of familiar cultural elements into the module fostered greater student motivation, authentic expression, and reflection, contributing not only to literacy development but also to cultural awareness and character education. These findings support the goals of Indonesia’s Independent Curriculum and highlight the pedagogical value of culturally responsive learning materials. The study offers practical implications for educators, curriculum developers, and policymakers in developing relevant instructional strategies grounded in local wisdom.